2023
DOI: 10.3389/fcimb.2023.1113643
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gut dominant microbiota in obese patients with nonalcoholic fatty liver disease

Abstract: In obese patients, non-alcoholic fatty liver (NAFLD) is common. However, whether there is a connection between the gut microbiota and the onset of NAFLD in obese people is yet unknown. Using quantitative real-time PCR, the microbiota of feces of the eligible 181 obese individuals was identified to compare the differences in gut microbiota between obesity with NAFLD and simple obesity. According to the findings, the gut dominant microbiota was similar between obesity with NAFLD and simple obesity. Nonetheless, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…In a study characterizing the dominant GM in obese patients with non-alcoholic fatty liver disease, the quantity of Faecalibacterium prausnitzii colonies was significantly lower in the obesity with non-alcoholic fatty liver disease group than in the simple obesity group. Additionally, F. prausnitzii is positively impacted by C. leptum 37 , suggesting that Leptum may be a protective bacterial group, consistent with our research findings. Du and colleagues discovered that a significant enrichment of the Clostridia class can enhance antigen presentation and effector T cell function through the cGAS-STING-IFN-I pathway, thereby boosting anti-tumor immune responses 38 .…”
Section: Discussionsupporting
confidence: 91%
“…In a study characterizing the dominant GM in obese patients with non-alcoholic fatty liver disease, the quantity of Faecalibacterium prausnitzii colonies was significantly lower in the obesity with non-alcoholic fatty liver disease group than in the simple obesity group. Additionally, F. prausnitzii is positively impacted by C. leptum 37 , suggesting that Leptum may be a protective bacterial group, consistent with our research findings. Du and colleagues discovered that a significant enrichment of the Clostridia class can enhance antigen presentation and effector T cell function through the cGAS-STING-IFN-I pathway, thereby boosting anti-tumor immune responses 38 .…”
Section: Discussionsupporting
confidence: 91%
“…In obesity, gut dysbiosis is related to changes in the diversity and composition of the gut microbiota. Dysbiosis can lead to increased energy harvesting from diet, metabolic disturbances, and inflammation associated with obesity [ 39 ], as dysbiosis in obesity is defined by a decrease in beneficial bacteria and an increase in harmful bacteria [ 40 ]. Similar to that in patients with obesity, gut dysbiosis has been associated with the pathogenesis of MAFLD.…”
Section: Gut–liver Axis In Mafldmentioning
confidence: 99%
“…One clinical study found that the abundance of Bacteroides increased as NAFLD pathology progressed, indicating a potential association between Bacteroides and NAFLD severity ( Boursier et al, 2016 ). Conversely, a study on obese patients with NAFLD showed a significant reduction in Bacteroides abundance ( Jin and Xu, 2023 ). In another study, compared to 28 healthy controls, 39 patients with biopsy-proven NAFLD had a prominently lower abundance of Bacteroides ( Da Silva et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%